Reinterpretasi Sila Pertama Pancasila melalui Pemikiran Politik John Calvin - Intan, Benyamin F (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
This editorial is a small step in an effort to reinterpret the first principle of Pancasila from the perspective of John Calvin's political thought. This effort was motivated by various acts of religious intolerance in Indonesia. This setting cannot be separated from the structural factors surrounding it: government intervention in internal religious affairs. Therefore, a reinterpretation of the first principle is urgently needed because this reinterpretation of the principle of Belief in One God can guarantee freedom of religion and the role of religion in the public sphere. In this way, religion can become a liberating force capable of creating democratic social and political life.